APPLICATION OF SYNTHETIC AND NATURAL POLYMERS IN PREPARATION AND CHARACTERIZATION OF DOMPERIDONE FAST-DISSOLVING FILMS - SARIPILLI RAJESWARI; PATIBANDLA SAMEERA; KONCHADA ALEKHYA; KURALLA HARI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present research work is mainly focused on solubility enhancement of domperidone which is a biopharmaceutical classification system Class II drug using natural and synthetic polymers. Methods: The solubility was enhanced by the kneading method with the drug: polymer (1:0.5, 1:0.75, and 1:1) using β-cyclodextrin. The fast dissolving films (FDFs) of domperidone were prepared by incorporating the solid dispersion (SD) SDK3 by solvent casting method using hydroxypropyl methylcellulose K15 M (HPMC) and gellan gum in various concentrations for preparing FDFs. Various pre- and post-compression parameters, drug and excipients compatibility studies were evaluated by Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), and X-ray diffraction analysis (XRD). Results: The maximum drug release of 98.86 % was achieved within 30 min for 1:1 ratio of solid dispersion using β-cyclodextrin, was optimized and taken for further development of FDFs. From the in vitro drug release studies films prepared with 10% w/w of HPMC K 15 (FH5) and 10% w/w of gellan gum (FG5) showed enhanced dissolution rate compared to other formulations. The formulation FHG with combination of polymers, namely, HPMC K 15 and gellan gum in 1:1 ratio showed drug release of 97.22% within 15 min only when compared with the optimized formulations. FTIR and DSC studies revealed that there were no interactions between drug and excipients. XRD studies revealed slight conversion of crystalline form to amorphous. The optimized formulation FHG found to be stable under accelerated stability studies. Conclusions: The polymers in combination are a potential candidate for use in the formulation of FDF.